IMPLEMENTASI KEBIJAKAN PENERAPAN KURIKULUM MUATAN LOKAL KESENIAN BETAWI PADA LINGKUNGAN PENDIDIKANFORMAL DI PROVINSI DKI JAKARTA - Rahmatulloh; , Rasminto; Candra Maulana; Khausar (Jurnal Genta Mulia, 2021)
This study aims to explain the implementation of the local content curriculum implementation policy for Betawi arts in the school environment in Jakarta. The method used is a descriptive study with a qualitative approach. Data were collected from interviews and focus group discussions with educational and community leaders who became research informants. The findings that can be concluded are first,the policy of learning the local content of Betawi arts as a means of transforming Jakarta's local culture has not been implemented effectively in a number of local government-owned schools, both at the junior and senior high school levels, so it still requires further guidance from the DKI Jakarta Provincial Government; second, there are still a number of traditional activities, the use of symbols or performances of Betawi cultural arts that are found in formal schools in DKI Jakarta; third, the tradition of using symbols and performing Betawi cultural arts supports and supports the policies of the DKI Jakarta Provincial Government and the community as cultural users.